2022
DOI: 10.1177/00236772221080833
|View full text |Cite
|
Sign up to set email alerts
|

Animal experiments in biomedical research: Knowledge, self-evaluation and attitudes of biology and medical students

Abstract: Animal experiments in biomedical research are debated in public, within the scientific community and among students. Despite increased efforts to reduce, refine and replace animal experiments, they remain integral components of the job of a biomedical scientist. In Germany, persons must have a university degree and adequate education and training to perform and direct animal experiments. Therefore, training courses such as FELASA (Federation of European Laboratory Animal Science Associations) courses are provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…13,33 Furthermore, Kanzler et al showed that medical-/biology students' knowledge of animal experimentation is limited, regardless of educational stage. 34 Certainly in the early phase of education, VR modules could replace working with live animals and generate sufficient initial experience in the field of laboratory animal science.…”
Section: Discussionmentioning
confidence: 99%
“…13,33 Furthermore, Kanzler et al showed that medical-/biology students' knowledge of animal experimentation is limited, regardless of educational stage. 34 Certainly in the early phase of education, VR modules could replace working with live animals and generate sufficient initial experience in the field of laboratory animal science.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies of allergic reactions mainly use animals as experimental subjects. Animal experiments are widely used in life science research and play an important role therein ( 58 ). Guinea pigs, BALB/c mice, Wistar rats, Sprague Dawley rats, Brown Norway rats, piglets, and dogs have been used in experimental anti-allergic studies ( 59 65 ).…”
Section: In Vitro and In Vivo Research Me...mentioning
confidence: 99%